Varieties of Capitalism and Institutional Complementarities in the Macroeconomy - Peter A. Hall; Daniel W. Gingerich (Max Planck Institute for the Study of Societies, 2004)
Using aggregate analysis, this paper examines the core contentions of the "varieties of capitalism" perspective on comparative capitalism. We construct a coordination index to assess whether the institutional features of liberal and coordinated market economies conform to the predictions of the theory. We test the contention that institutional complementarities occur across sub-spheres of the macroeconomy by examining the correspondence of institutions across sub-spheres and estimating the impact of complementarities in labor relations and corporate governance on rates of growth. To assess the stability of the institutional features central to the theory, we assess the dynamics of institutional change in recent years. The evidence suggests that there are powerful interaction effects among institutions across sub-spheres of the political economy that must be considered if the economic impact of institutional change in any one sphere is to be accurately assessed. – – Mit Hilfe von Aggregatdaten analysiert dieses Papier Kernaussagen des "Varieties-of-Capitalism"-Ansatzes. Um beurteilen zu können, ob die Aussagen der Theorie mit den institutionellen Begebenheiten liberaler und koordinierter Ökonomien übereinstimmen, konstruieren wir einen ländervergleichenden Index der ökonomischen Koordination. Wir überprüfen die These von der institutionellen Komplementarität zwischen den verschiedenen Sphären politischer Ökonomien, indem wir das Zusammenwirken von Institutionen analysieren und den Einfluss komplementärer Institutionen der Arbeitsbeziehungen und der Unternehmenskontrolle auf die Höhe von Wachstumsraten untersuchen. Wir diskutieren darüber hinaus, wie stabil die institutionellen Begebenheiten in den vergangenen Jahren waren. Im Ergebnis zeigen sich starke Interaktionseffekte zwischen den Sphären politischer Ökonomien, die berücksichtigt werden müssen, um die wirtschaftlichen Wirkungen institutionellen Wandels in einzelnen Sphären zu verstehen.
Keywords: 300